2015
DOI: 10.4103/2153-3539.151922
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the CellaVision® DM96 system for detecting red blood cell morphologic abnormalities

Abstract: Background:Red blood cell (RBC) analysis is a key feature in the evaluation of hematological disorders. The gold standard light microscopy technique has high sensitivity, but is a relativity time-consuming and labor intensive procedure. This study tested the sensitivity and specificity of gold standard light microscopy manual differential to the CellaVision® DM96 (CCS; CellaVision, Lund, Sweden) automated image analysis system, which takes digital images of samples at high magnification and compares these imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…RBC overlap is sometimes falsely reported by the CellaVision as macrocytosis 5,6,16 A low sensitivity of 33% for RBC agglutination has been reported by Horn et al 31 They also reported high specificities but variable sensitivities for RBC morphologic abnormalities using the DM96. Sensitivity for sickle cells and stomatocytes reached 100%.…”
Section: Red Blood Cell Morphology and The Cellavision Arbcamentioning
confidence: 95%
“…RBC overlap is sometimes falsely reported by the CellaVision as macrocytosis 5,6,16 A low sensitivity of 33% for RBC agglutination has been reported by Horn et al 31 They also reported high specificities but variable sensitivities for RBC morphologic abnormalities using the DM96. Sensitivity for sickle cells and stomatocytes reached 100%.…”
Section: Red Blood Cell Morphology and The Cellavision Arbcamentioning
confidence: 95%
“…1 Another study analyzed 15 RBC morphologies, but reported results as present or absent, which is not our practice. 2 Criel et al 3…”
Section: Assessment Of Semi-quantitative Grading Of Red Blood Cell Abmentioning
confidence: 99%
“…Evaluation of white blood cell (WBC) morphology by these automated analyzers has a higher level of accuracy and precision compared to manual morphological assessment by microscope. Several performance evaluations of these platforms have been carried out, but mostly with the main focus on the leukocytes .…”
Section: Introductionmentioning
confidence: 99%